Truth, Half-Truth, and Post-Truth: lessons from William James - Araújo, Saulo de Freitas (Journal of Constructivist Psychology, 2022)
According to many authors, we live in a post-truth era, to the extent that truth has become subordinated to politics. This has implications not only to political debates, but also to science, technology, and common sense thinking. In this paper, I claim that William James’s conception of truth may shed new light on the contemporary post-truth debate. First, I will present the essential elements of James’s initial position. Then, I will discuss some of his amendments to clarify and improve his theory to avoid misunderstandings. Finally, I will address his potential contributions to the contemporary post-truth debate, and consider whether there are special implications for psychology.